Effect of Deuterium Depletion on Erythrocytes in_x000D_ Experimental Diabetes - YARAT, AYŞEN (My University, 2020)
In the development of diabetic complications, oxidative stresscaused by hyperglycemia plays an important role. Deuterium depletionhas protective effect against cellular damage and tumorsuppressor effect in cancer cell lines. The purpose of this studywas to examine and evaluate the effect of deuterium depletion onerythrocyte oxidant and antioxidant system parameters in experimentaldiabetes induced by streptozotocin (STZ) in rats. On the30th or 40th day after STZ injection, blood samples were taken andblood glucose levels were measured. Erythrocyte hemolysateswere also prepared. Lipid peroxidation and glutathione levels andglutathione-S-transferase, superoxide dismutase and catalase enzymeactivities of erythrocytes were determined. At the 30 or 40day periods, deuterium depleted water (DDW) consumption haddifferently affected oxidant-antioxidant parameters of erythrocytes.The clear effect of deuterium depletion in drinking waterfrom 150 ppm to 85 ppm was observed in glutathione levels andit increased erythrocyte glutathione levels in both the control anddiabetic groups. In conclusion, deuterium depletion may have protectiveeffects on diabetes induced oxidative stress. Further studiesare needed to be done to determine the mechanism of actionand the useful dosage and the application period of DDW.

Diabetik komplikasyonların gelişmesinde, hiperglisemi kaynaklı_x000D_ oksidatif stres çok önemli bir rol oynamaktadır. Döteryum azlığının_x000D_ hücresel hasara karşı ve tümör baskılayıcı etki üzerine koruyucu_x000D_ etkisi olduğu kanser hücre hatlarında gösterilmiştir. Çalışmanın_x000D_ amacı, döteryum azaltılmasının sıçanlarda streptozotosin (STZ) ile_x000D_ oluşturulmuş deneysel diabette eritrosit oksidan ve antioksidan_x000D_ sistem parametreleri üzerindeki etkisinin araştırılması ve değerlendirilmesidir._x000D_ STZ enjeksiyonunu takiben 30. veya 40. günde, kan_x000D_ örnekleri alınıp, kan glukoz değerleri ölçülmüş, eritrosit hemolizatları_x000D_ da hazırlanmıştır. Eritrositlerin lipid peroksidasyon ve glutatyon_x000D_ seviyeleri ile glutatyon-S-transferaz, süperoksit dismutaz ve katalaz_x000D_ enzim aktiviteleri tayin edilmiştir. 30 veya 40 günlük periyotlardaki_x000D_ döteryumu azaltılmış su tüketiminin, eritrosit oksidan-antioksidan_x000D_ parametre düzeylerine etkisinin farklı olduğu görülmüştür. İçme_x000D_ suyunda döteryumun 150 ppm den 85 ppm’e azaltılmasının net_x000D_ etkisi glutatyon düzeylerinde gözlenmiş olup hem kontrol hem_x000D_ de diyabetik gruplarda eritrosit glutatyon düzeylerini artırdığı saptanmıştır._x000D_ Sonuç olarak, döteryumu azaltılmış suyun, diabete bağlı_x000D_ oksidatif hasara karşı koruyucu etkisi olabilir. Döteryumu azaltılmış_x000D_ suyun etki mekanizmasının, uygun dozunun ve uygulama süresinin_x000D_ aydınlatılması için daha fazla çalışmalara ihtiyaç vardır.
Deneysel Diyabette Döteryum Azlığının Eritrositler Üzerine Etkisi